BTT & RFLB - THE OPTIMUM SET FOR STEAM TURBINE BLADES MONITORING - Miroslav Balda (Acta Polytechnica CTU Proceedings, 2018)
BTT, Blade Tip Timing system, is a commercially available system generating files of precise times of blade tips when passing sensors attached in a machine stator. RFLB, Residual Fatigue Life of Blades, is a postprocessor of those files evaluating estimates of fatigue lives of all blades fitted to the wheel. The set reduces a danger of unexpected blade failures.